2015
DOI: 10.1097/icu.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Management of orbital IgG4-related disease

Abstract: The management of orbital IgG4-RD will gain from more targeted therapy in the future as the underlying cause is better understood. In the meantime, randomized, controlled trials of varying treatment regimens would be of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The standard treatment for both IgG4-RD and IgG4-ROD is oral steroids,7 14 15 but the disease has a high recurrence rate. Ebbo et al reported that 13 of 19 cases (68.4%) of IgG4-ROD relapsed after the first course of oral steroids 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard treatment for both IgG4-RD and IgG4-ROD is oral steroids,7 14 15 but the disease has a high recurrence rate. Ebbo et al reported that 13 of 19 cases (68.4%) of IgG4-ROD relapsed after the first course of oral steroids 16.…”
Section: Discussionmentioning
confidence: 99%
“…Oral steroid administration is the first-line therapy for IgG4-ROD and patients generally exhibit a good treatment response. However, recurrence occurs in more than half of the patients during oral steroid dose tapering, prolonging treatment and subsequently increasing the risk of steroid-related complications 7–9. Therefore, alternative therapies, including immunosuppressive drugs and rituximab, have been examined and validated 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the patient's ocular symptoms recurred under oral immunosuppressants including azathioprine, hydroxychloroquine, and prednisolone. Elevated IgG4 level was also detected, which suggested a more complicated clinical situation that might be responsive to higher dose of steroids [13]. The repeated use of IV pulse steroid treatments did not lead to any recurrence of generalized MG, but resulted in full recovery of the ocular symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…Meanwhile, steroid-induced symptom exacerbation should be taken into consideration while initially treating the relatively elderly patients with severe MG [7]. However, the phenomenon of persistent ocular symptoms disappeared after repeated doses of IV pulse steroid, indicating that early deterioration should not preclude this beneficial treatment option during later followups of these patients [13]. We propose that the IV pulse steroid treatments were even more indicated if an IgG4 disease co-exists with MG and thyroid-associated orbitopathy.…”
Section: Resultsmentioning
confidence: 99%
“…A diagnózis felál-lításában, a jellegzetes klinikai tünetek mellett, az emelkedett IgG 4 -szint segít, de a szövettani vizsgálat minden esetben elengedhetetlen, amely az érintett szervben IgG 4 -pozitív plazmasejt-infiltrációt mutat. Az első vá-lasztandó terápia az orális kortikoszteroid, amelyre álta-lában gyors és látványos javulás észlelhető, míg súlyo-sabb esetekben biológiai kezelésre (rituximab) lehet szükség [11][12][13][14].…”
unclassified